2007
DOI: 10.1073/pnas.0700763104
|View full text |Cite
|
Sign up to set email alerts
|

Protease-activated receptor-3 (PAR3) regulates PAR1 signaling by receptor dimerization

Abstract: Thrombin activates endothelial cell signaling by cleaving the protease-activated receptor-1 (PAR1). However, the function of the apparently nonsignaling receptor PAR3 also expressed in endothelial cells is unknown. We demonstrate here the crucial role of PAR3 in potentiating the responsiveness of PAR1 to thrombin. We tested the hypothesis that PAR1/PAR3 heterodimerization and its effect in modifying G protein selectivity was responsible for PAR3 regulation of PAR1 sensitivity. Using bioluminescent resonance en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
165
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(171 citation statements)
references
References 37 publications
5
165
0
1
Order By: Relevance
“…The co-immunoprecipitation and FRET data demonstrate that PAR1 self-associates to form a homodimer or homooligomer, consistent with previous BRET experiments in HEK cells (55). Although the exact structure and relative orientation of the homodimer are difficult to determine with certainty, the direct binding data presented here indicate that a stable homodimer may form with each i3 loop interacting with an H8 helix across the dimer interface.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The co-immunoprecipitation and FRET data demonstrate that PAR1 self-associates to form a homodimer or homooligomer, consistent with previous BRET experiments in HEK cells (55). Although the exact structure and relative orientation of the homodimer are difficult to determine with certainty, the direct binding data presented here indicate that a stable homodimer may form with each i3 loop interacting with an H8 helix across the dimer interface.…”
Section: Discussionsupporting
confidence: 89%
“…homodimer (55) in HEK cells. Similarly, PAR1 has been documented to heterodimerize with the closely related PAR2 and PAR4 receptors on endothelial cells and/or platelets (22,26).…”
Section: The I3 Loop Pepducin and Thrombin Induce Conformational Chanmentioning
confidence: 99%
“…PAR3 suppression resulted in ϳ50% reduction of transendothelial electrical resistance, while PAR1 suppression completely reduced transendothelial electrical resistance in response to thrombin. Based on bioluminescent resonance energy transfer-2 measurements, the authors concluded that PAR3 dimerizes with and regulates PAR1 signaling (65). Our data, illustrating that (i) PAR1AP and PAR4AP fail to promote cellular responses in A549 cells, (ii) PAR3 is the only PAR transcript present in these cells, and (iii) PAR3 siRNA decreased thrombin-evoked responses, indicate that PAR3 is the major thrombin receptor functionally present in these cells.…”
Section: Discussionmentioning
confidence: 63%
“…Thrombin is known to induce permeability through PAR-1 which heterodimerizes with PAR-3 leading to G a13 -dependent calcium signaling, actin stress fiber formation and transient increases in endothelial permeability. 70 Moreover, a subset of parasites from patients with CM has been shown to bind to EPCR, and may compete with APC for the binding to this receptor. 55,71,72 As APC exerts a protective effect on thrombin induced barrier dysfunction, IRBC adhesion may exaggerate the barrier dysfunction elicited by thrombin.…”
Section: Cytoadherencementioning
confidence: 99%